2017
DOI: 10.3945/ajcn.117.156943
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin responsiveness varies across the population dependent on metabolic phenotype

Abstract: Cholecystokinin (CCK) is an important satiety factor, acting at type 1 receptors (CCK1Rs) on vagal afferent neurons; however, CCK agonists have failed clinical trials for obesity. We postulated that CCK1R function might be defective in such patients due to abnormal membrane composition, such as that observed in cholesterol gallstone disease. Due to the challenges in directly studying CCK1Rs relevant to appetite control, our goal was to develop and apply a method to determine the impact of a patient's own cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…Cholecystokinin (CCK) is a satiety factor, acting at type 1 receptors (CCK1Rs) on vagal afferent neurons [19]. Therefore, its role in the treatment of obesity has been studied in trials with negative results.…”
Section: Role Of Gastrointestinal Peptides In Eating Behavior and Itsmentioning
confidence: 99%
“…Cholecystokinin (CCK) is a satiety factor, acting at type 1 receptors (CCK1Rs) on vagal afferent neurons [19]. Therefore, its role in the treatment of obesity has been studied in trials with negative results.…”
Section: Role Of Gastrointestinal Peptides In Eating Behavior and Itsmentioning
confidence: 99%
“…However, in this study (Desai et al, ), no standard clinical, biochemical or morphometric parameters, alone or in combination, were found to be adequate to identify those subjects exhibiting this defect in CCK responsiveness. Another key finding was that the CCK sensitivity was best correlated with different types of lipids in patients with different BMIs.…”
Section: The Cck1 Receptor As An Exemplar Of a Metabolically Importanmentioning
confidence: 63%
“…In a recent study (Desai et al, ), we have developed a technique that enables the study of CCK 1 receptor function in a patient's own cell membrane micro‐environment. In this work, the CCK 1 receptor was expressed ex vivo in leukocytes collected from patients using an adenoviral construct, in order to measure its function.…”
Section: The Cck1 Receptor As An Exemplar Of a Metabolically Importanmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that insulin can suppress hepatic bile acid biosynthesis through the forkhead transcription factor O1 (FoxO1)/small heterodimer partner (Shp)/cholesterol 7α‐hydroxylase (Cyp7a1) axis or by targeting Cyp8b1 expression . The inverse correlation between BA levels and insulin secretion may result from the inhibitory effect of insulin on hepatic BA synthesis and transport or, alternatively, from the effects of BAs on β‐cell function directly or indirectly via its effects on islet α‐cells, enteroendocrine cells, or other BA‐target organs, such as the liver or adipose tissue …”
Section: Discussionmentioning
confidence: 99%